Copper mining: 100% solar electricity by 2030?. (15th March 2020) - Haas, Jannik; Moreno-Leiva, Simón; Junne, Tobias; Chen, Po-Jung; Pamparana, Giovanni; Nowak, Wolfgang; Kracht, Willy; Ortiz, Julián M.
Highlights: We calculate the optimal electricity supply for large copper mines around the world. From 2020 onwards, all mines should have solar shares above 25%. In 2030, the first fully solar mines should be established. In the long-term, Chile and Peru have the lowest electricity costs. In most locations, low-cost solar energy makes up for costs from declining ore grades. Abstract: Extracting copper is energy-intensive. At the same time, copper is a key material for building the energy systems of the future. Both facts call for clean copper production. The present work addresses the greenhouse gas emissions of this industry and focuses on designing the future electricity supply of the main copper mines around the world, from 2020 to 2050, using distributed solar photovoltaic energy, storage, and a grid connection. We also consider the increasing energy demand due to ore grade decline. For the design, we use an optimization model called LEELO. Its main inputs are an hourly annual demand profile, power-contract prices for each mine, cost projections for energy technologies, and an hourly annual solar irradiation profile for each mine. Our findings show that it is attractive for the mines to have today a solar generation of 25% to 50% of the yearly electricity demand. By 2030, the least-cost solution for mines in sunny regions will be almost fully renewable, while in other regions it will take until 2040. The expected electricity costs range from 60 to100 €/MWh for 2020 and from 30 to 55 €/MWh for 2050, with the lower bound in sunny regions such as Chile and Peru. In most locations assessed, the low cost of solar energy will compensate for the increased demand due to declining ore grades. For the next steps, we recommend representing the demand with further detail, including other vectors such as heat and fuels. In addition, we recommend to include the embodied emissions of the technologies to get a more complete picture of the environmental footprint of the energy supply for copper production.